2015
DOI: 10.1111/bjdp.12120
|View full text |Cite
|
Sign up to set email alerts
|

Perceived discrimination amongst young people in socio‐economically disadvantaged communities: Parental support and community identity buffer (some) negative impacts of stigma

Abstract: There is increasing acceptance that children are not unaware of when they are targets of discrimination. However, discrimination as a consequence of socio‐economic disadvantage remains understudied. The aim of this study was to examine the impact of perceived discrimination on well‐being, perceptions of safety and school integration amongst children growing up within socio‐economically disadvantaged communities in Limerick, Ireland. Mediation analysis was used to explore these relationships and to examine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 69 publications
0
13
0
2
Order By: Relevance
“…Prior research has found a positive correlation between community identity and the factors involving interdependence, such as social support (McNamara et al, 2013), school integration (Bradshaw et al, 2016), and mutual helping (Yang & Xin, 2016). For example, Yang and Xin (2016) demonstrated that the likelihood of helping being offered in an emergency was promoted as community identity increased among Chinese residents.…”
Section: Independent Versus Interdependent Self-construal and Communimentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research has found a positive correlation between community identity and the factors involving interdependence, such as social support (McNamara et al, 2013), school integration (Bradshaw et al, 2016), and mutual helping (Yang & Xin, 2016). For example, Yang and Xin (2016) demonstrated that the likelihood of helping being offered in an emergency was promoted as community identity increased among Chinese residents.…”
Section: Independent Versus Interdependent Self-construal and Communimentioning
confidence: 99%
“…Over the years, increasing research has explored what causes some community members to highly identify with the community and frequently engage in community activities, whereas others do not (Bradshaw, Jay, McNamara, Stevenson, & Muldoon, ; Christens, Speer, & Peterson, ; Obst & White, ; Xin & Ling, ). Specifically, community identity and community participation have been demonstrated to be closely associated with the factors involving interdependence, such as interpersonal relationships (Christens, , ), social support (McNamara, Stevenson, & Muldoon, ), sense of community (Xin & Ling, ), and social capital (Xu, Perkins, & Chow, ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study focused on how an emerging community of Latino/a immigrants in a city understood and responded to discrimination, which actively shaped the Latino/a identity within their own community (Macia, 2016). More research should compare the effects of community identity and ethnic identity as stress buffers against discrimination to establish the extent to which they are resources that protect the individual and community well-being (Bradshaw, Jay, McNamara, Stevenson, & Muldoon, 2015). More research should compare the effects of community identity and ethnic identity as stress buffers against discrimination to establish the extent to which they are resources that protect the individual and community well-being (Bradshaw, Jay, McNamara, Stevenson, & Muldoon, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Distinguishing between community identity and social identity, such as ethnic identity, can be difficult because they both encompass how belongingness, inclusion, and exclusion are established (Puddifoot, 1996, p. 328). More research should compare the effects of community identity and ethnic identity as stress buffers against discrimination to establish the extent to which they are resources that protect the individual and community well-being (Bradshaw, Jay, McNamara, Stevenson, & Muldoon, 2015). Moreover, ethnic identities can provide social support and feelings of collective efficacy that can be impetuses for collective action, which can ultimately transform communities (McNamara, Stevenson, & Muldoon, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Group identification can reduce isolation and help us to cope with prejudice, stigma and rejection of negative stereotypes by emphasising that which is shared with other group members (Schmitt et al, ). It can buffer against threats to our well‐being (Schmid & Muldoon, ); allow us to harness psychological resources necessary to cope with the negative consequences of being a member of a devalued group (Bradshaw, Jay, McNamara, Stevenson, & Muldoon, ) and provide a platform for emotional bonding and the giving and receiving of social support (Haslam et al, ; Iyer, Jetten, Tsivrikos, Postmes, & Haslam, ). In this way, identity processes can be seen to off‐set some of the consequences of negative experiences and positively impact psychological well‐being (Haslam et al, ).…”
mentioning
confidence: 99%